Bioethics and imagination: towards a narrative bioethics committed to social action and justice. Issue 3 (13th January 2017) - Manchola Castillo, Camilo Hernán; Solbakk, Jan Helge
Abstract : Recently, the involvement of various authors coming from the social sciences and the arts has reinforced the humanistic component of bioethics. Their contributions vary from very theoretical perspectives to rather practical ones. In this paper, Martha Nussbaum's books, The Fragility of Goodness (1986), Love's Knowledge (1990), Cultivating Humanity (1997) and Creating Capabilities (2011) are analysed from the vantage point of narrative bioethics. It is argued that Nussbaum's notions of 'Narrative', 'Imagination' and 'Cultivation' open up the possibility of developing an action-oriented form of narrative bioethics, that is, a bioethics committed to social action and justice.